A population‐based study on combined markers for early Parkinson's disease. Issue 4 (27th December 2014) - Tunc, Sinem; Graf, Julia; Tadic, Vera; Brüggemann, Norbert; Schmidt, Alexander; Al‐Khaled, Mohamed; Wolff, Simone; Vollstedt, Eva‐Juliane; Lorwin, Anne; Hampf, Jennie; Piskol, Linda; Klein, Christine; et al.
Abstract The prerequisite for an earlier diagnosis of Parkinson's disease (PD) are markers that are both sensitive and specific for clinically definite PD and its prediagnosic phases. Promising candidates include enlarged hyperechogenicity of the substantia nigra (SN+) on transcranial sonography (TCS) and hyposmia. However, despite good sensitivity and specificity, both markers have yet failed to yield reliable predictions. We pursue the possibility of combined use in an ongoing population‐based cohort. Subjects were recruited from 10, 000 inhabitants of Luebeck/Germany aged 50 to 79 years and additional PD patients from our outpatient clinic. After neurological examination, 715 subjects were grouped into clinically definite PD (n = 106), possible prediagnostic PD (ppPD; n = 73), and a control group subdivided into healthy individuals (n = 283) and controls with diseases other than PD (n = 253). Subjects underwent TCS and smell testing. Sensitivity and specificity of SN+ and hyposmia were good for PD; however, positive predictive values (PPV) of both SN+ (5.2%) and olfaction (2.5%) were low. At least one positive/both positive markers were present in 33%/1% of healthy controls, 33%/2% of diseased controls, 62%/7% of ppPD, and 94%/51% of PD. When combining SN+ and hyposmia, PPV increased to 17.6%, with a sensitivity of 51% and a specificity of 98%. Both SN+ and hyposmia offer good enrichment towards PD and ppPD, are stable against other diseases, and the combination of markers highly increases specificity. However, if the combination of SN+ and hyposmia were used as criterion for PD diagnosis, almost half of clinically definite PD and more than 90% of ppPD would have been missed. © 2014 International Parkinson and Movement Disorder Society